2019
DOI: 10.3791/59063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Bioconjugation of Thiol-Reactive Reagents for the Creation of Site-Selectively Modified Immunoconjugates

Abstract: Maleimide-bearing bifunctional probes have been employed for decades for the site-selective modification of thiols in biomolecules, especially antibodies. Yet maleimide-based conjugates display limited stability in vivo because the succinimidyl thioether linkage can undergo a retro-Michael reaction. This, of course, can lead to the release of the radioactive payload or its exchange with thiol-bearing biomolecules in circulation. Both of these processes can produce elevated activity concentrations in healthy or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In this investigation, we have harnessed an emergent, thiol-reactive bioconjugation reagent based on a p henyl o xa d iazolyl methyl s ulfone (PODS) core to create a site-specifically modified 89 Zr-radioimmunoconjugate as a companion diagnostic for a DLL3-targeted antibody–drug conjugate (ADC). PODS-based reagents react quickly, cleanly, and (unlike maleimides) irreversibly with thiols (Figure A). Even more importantly, we have previously demonstrated that the site-selective modification of wild-type antibodies with PODS-bearing chelators produces 177 Lu- and 89 Zr-labeled radioimmunoconjugates with high stability and excellent in vivo performance (Figure B) …”
mentioning
confidence: 99%
“…In this investigation, we have harnessed an emergent, thiol-reactive bioconjugation reagent based on a p henyl o xa d iazolyl methyl s ulfone (PODS) core to create a site-specifically modified 89 Zr-radioimmunoconjugate as a companion diagnostic for a DLL3-targeted antibody–drug conjugate (ADC). PODS-based reagents react quickly, cleanly, and (unlike maleimides) irreversibly with thiols (Figure A). Even more importantly, we have previously demonstrated that the site-selective modification of wild-type antibodies with PODS-bearing chelators produces 177 Lu- and 89 Zr-labeled radioimmunoconjugates with high stability and excellent in vivo performance (Figure B) …”
mentioning
confidence: 99%
“…The radiosynthesis of the novel reagents is summarized in Schemes – , while the synthesis of Boc 2 - iso -SGMIB, Boc 2 - iso -SGMTB, and PODS has been reported before. ,, The synthesis of DOTA-PODS followed a modified method using p -SCN-Bn-DOTA (Macrocyclics, Inc, Texas). The conjugations of Boc 2 - iso -SGMIB and Boc 2 - iso -SGMTB to PODS were performed under basic conditions using a common protocol.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Zeglis and co-workers adopted this linker to generate a conjugate of trastuzumab and a radionuclide chelator 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA). 118 The antibody was incubated with 10 equiv. of PODS–DOTA for 2 h at room temperature and yielded the conjugate with 80% yield.…”
Section: Bioconjugation Methods For Adc Linkermentioning
confidence: 99%